2022
DOI: 10.1038/s41388-022-02530-4
|View full text |Cite
|
Sign up to set email alerts
|

EXOSC8 promotes colorectal cancer tumorigenesis via regulating ribosome biogenesis-related processes

Abstract: Extensive protein synthesis is necessary for uncontrolled cancer cell proliferation, requiring hyperactive ribosome biogenesis. Our previous Pan-cancer study has identified EXOSC8 as a potential copy number variation (CNV)-driven rRNA metabolism-related oncogene in colorectal cancer (CRC). Herein, we further investigated proliferation-prompting functions and mechanisms of EXOSC8 in CRC by performing in silico analyses and wet-lab experiments. We uncovered that increased EXOSC8 expression and CNV levels are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…CX-5461, an RNA polymerase I inhibitor, can inhibit ribosome biogenesis, leading to growth, migration, and DNA damage induction in pancreatic ductal adenocarcinoma cells [21]. Silencing of the rRNA metabolism-associated cancer gene EXOSC8 reduces levels of nucleolar proteins and proliferation markers, as well as rRNA/DNA and global protein synthesis, inhibiting colorectal cancer cell proliferation [22]. These studies suggest that ribosome stress causes a series of disruptions in cellular biology.…”
Section: Discussionmentioning
confidence: 97%
“…CX-5461, an RNA polymerase I inhibitor, can inhibit ribosome biogenesis, leading to growth, migration, and DNA damage induction in pancreatic ductal adenocarcinoma cells [21]. Silencing of the rRNA metabolism-associated cancer gene EXOSC8 reduces levels of nucleolar proteins and proliferation markers, as well as rRNA/DNA and global protein synthesis, inhibiting colorectal cancer cell proliferation [22]. These studies suggest that ribosome stress causes a series of disruptions in cellular biology.…”
Section: Discussionmentioning
confidence: 97%
“…For example, DDX17 was reported to serve as inflammasome sensor for SINE RNAs [ 68 ], and consistently down-regulated DDX17 may contribute to immune escape. Regarding the hallmarks of genomic alterations related to RiboSis, our multi-omic data revealed that the main genetic variation of RiboSis genes was CNV, suggesting that high-level amplification of RiboSis genes in tumors may be one of the main driving factors for hyperactive RiboSis [ 69 , 70 ]. Concerted copy number variation balances are important for ribosomal DNA [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent steps were completed using the GT Vision III Detection System (GeneTech, China). H&E and IHC staining assays were carried out according to our previous methods 8,14,16 …”
Section: Methodsmentioning
confidence: 99%
“…Images were captured by a confocal microscope (ZEISS, LSM880, Germany). The detailed operation method can be found in our previous study 13,14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation